2018
DOI: 10.1021/acsami.8b16333
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Self-Assembly of Au Nanoparticles on Rigid Mesoporous Yeast-Based Microspheres for Sensitive Immunoassay

Abstract: A simple, rapid, inexpensive, eco-friendly, and high-throughput biological strategy for the preparation of functional microspheres on a yeast-cell platform was introduced. Microspheres prepared through the treatment of yeast cells with formaldehyde and decoating buffer exhibited excellent characteristics, such as superior mechanical strength, high sulfhydryl group content, and mesoporous structure. Au nanoparticles (NPs) easily and rapidly self-assembled onto the surfaces of the yeast-based microspheres within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…As shown in Figure B, it can be confirmed that the presence of – COOH groups (3306 and 1652 cm –1 ), −NH 2 groups (1652 and 1539 cm –1 ), – OH groups (3306, 2927, and 1049 cm –1 ), and −SH groups (1049 and 700 cm –1 ) on the yeast cell wall. The presence of various functional groups on the surface of yeast will provide a wide range of fixed sites to stabilize various metals (e.g., Zr 4+ ) and molecules . After the formation of yeast@UiO-66-NH 2 composites, red-shift and blue-shift occurred at multiple peaks.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…As shown in Figure B, it can be confirmed that the presence of – COOH groups (3306 and 1652 cm –1 ), −NH 2 groups (1652 and 1539 cm –1 ), – OH groups (3306, 2927, and 1049 cm –1 ), and −SH groups (1049 and 700 cm –1 ) on the yeast cell wall. The presence of various functional groups on the surface of yeast will provide a wide range of fixed sites to stabilize various metals (e.g., Zr 4+ ) and molecules . After the formation of yeast@UiO-66-NH 2 composites, red-shift and blue-shift occurred at multiple peaks.…”
Section: Resultsmentioning
confidence: 98%
“…As one of the most commonly used multiplex technologies, microsphere-based flow-cytometry (e.g., suspension array) has attracted considerable interest in modern diagnostics for precise medicine. , The preparation of encoded microspheres with homogeneous physiochemical properties and enhanced sensitivities is essential for microsphere-based analysis methods in basic and technological research . To date, there are two main coding systems, including spectroscopic, and graphical encoding that have been presented to provide a sufficient number of identification codes for microspheres.…”
mentioning
confidence: 99%
See 3 more Smart Citations